2016
DOI: 10.1016/j.msard.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative visual tests after poorly recovered optic neuritis due to multiple sclerosis

Abstract: Background Visual dysfunction in MS can be quantified using a variety of tests. Many vision tests have not been formally evaluated among MS patients with existing visual dysfunction. Objective Evaluate several versions of visual acuity and contrast sensitivity tests, measures of central and peripheral vision, retina structure, electrophysiologic function, and quality of life among MS patients with moderate/severe visual dysfunction. Methods Cross-sectional study of 46 patients with stable, incompletely rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…It is well established that CS and low-contrast letter chart are more sensitive than high contrast acuity in detecting visual deficits in MS/ON and both correlate strongly with RNFLT (Fisher et al, 2006, Longbrake et al, 2016, Balcer et al, 2017). The Pelli-Robson CS chart uses large letters with a fixed size (2.8° at 1 meter) but descending contrasts, allowing CS to be measured in eyes with impaired vision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that CS and low-contrast letter chart are more sensitive than high contrast acuity in detecting visual deficits in MS/ON and both correlate strongly with RNFLT (Fisher et al, 2006, Longbrake et al, 2016, Balcer et al, 2017). The Pelli-Robson CS chart uses large letters with a fixed size (2.8° at 1 meter) but descending contrasts, allowing CS to be measured in eyes with impaired vision.…”
Section: Discussionmentioning
confidence: 99%
“…The Pelli-Robson CS chart uses large letters with a fixed size (2.8° at 1 meter) but descending contrasts, allowing CS to be measured in eyes with impaired vision. A recent study reported that 98% of MS eyes with residual visual deficits from ON could read at least two triplets of letters on the Pelli-Robson chart but more than half of them could not read any letters on the 2.5% low contrast letter chart (floor effect) (Longbrake et al, 2016). The good correlation observed between CS and structural measures (GCIPLT and RNFLT) in the current study further supports the clinical utility of Pelli-Robson chart in MS/ON eyes.…”
Section: Discussionmentioning
confidence: 99%
“…VEP amplitude is considered to be a biomarker of axonal integrity ( You et al, 2012 ) or function and correlates with visual recovery in patients following optic neuritis ( Halliday et al, 1977 , Hickman et al, 2004 , Longbrake et al, 2016 ). This contrasts with latency measures, which remain delayed despite the improvement of VEP amplitude and visual acuity ( Youl et al, 1991 ).…”
Section: Pathophysiological Insights From Vepmentioning
confidence: 99%
“…Despite the current challenge facing the inclusion of a QoL endpoint that captures the impacts of vision function in a clinical trial, the importance of finding a way forward is clear 44 45. Multiple studies, including our own large cohort (n=267), report a statistical association between instruments measuring QoL (54-item Multiple Sclerosis Quality of Life Scale score, 39-item NEI-VFQ, NEI-VFQ-25 and the 10-item Neuro-Ophthalmic supplement) and OCT atrophy measures 45–49. Many studies also report an association between vision-related QoL and other measures of vision function.…”
Section: Evidence On the Impact Of On On Qolmentioning
confidence: 99%